2017
DOI: 10.1016/j.fct.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for a systematic review to identify allergenic tree nuts and the molecules responsible for their allergenic properties

Abstract: Food regulations require that tree nuts and derived ingredients are included on food labels in order to help individuals with IgE-mediated allergies to avoid them. However, there is no consensus regarding which tree nut species should be included in this definition and specified on food labels. Allergen detection methods used for monitoring foods target allergen molecules, but it not clear which are the most relevant molecules to choose. A modified population-exposure-comparators-outcome (PECO) approach has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Among the many possible adverse reactions, food allergy appears to be of recent concern. The estimation of food allergy prevalence is difficult and has been suggested to be in the range from 3–6 to <10 and >10% in some regions. According to the National Institute of Allergy and Infectious Diseases (NIAID) expert panel, food allergy is defined as “an adverse health effect arising from a specific immune response that occurs reproducibly on exposure to a given food”. The adverse reaction to a food by the affected human involves complex chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many possible adverse reactions, food allergy appears to be of recent concern. The estimation of food allergy prevalence is difficult and has been suggested to be in the range from 3–6 to <10 and >10% in some regions. According to the National Institute of Allergy and Infectious Diseases (NIAID) expert panel, food allergy is defined as “an adverse health effect arising from a specific immune response that occurs reproducibly on exposure to a given food”. The adverse reaction to a food by the affected human involves complex chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, autoimmune injury was induced with plasma membrane antigen that extracted from the skeletal muscle and its nearby cutaneous tissues. Autoimmune injury consists of tissue damage resulting from immunological mechanisms; the four types of hypersensitivity always play roles in the pathogenesis of autoimmune disorders: i) Type I-immunoglobulin (Ig) E and mast cells; ii) type II-IgM, IgG and complement; iii) type III-IgG immunocomplexes; and type IV T lymphocytes and macrophages (34)(35)(36). In the present study, 14 days after membrane antigen stimulation, positive precipitation lines were observed in agar immunodiffusion assays carried out in randomly selected rats.…”
Section: Discussionmentioning
confidence: 99%
“…We used the list of tree nuts and legumes adapted from Javed et al. (2017) and Semba et al. (2021), so there were 30 keywords in each database as terms without further restrictions applied to the search (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…To provide a global assessment, we also searched the literature using the specific name of tree nuts and legumes as the basis for defining the search terms. We used the list of tree nuts and legumes adapted from Javed et al (2017) and Semba et al (2021), so there were 30 keywords in each database as terms without further restrictions applied to the search (Table 1).…”
Section: Search Strategymentioning
confidence: 99%